THE IMPACT OF CORPORATE GOVERNANCE AND FAMILY OWNERSHIP ON CSR REPORTING QUALITY: EVIDENCE FROM THE MALAYSIAN STOCK EXCHANGE - Ghuslan, Mohamad Iruwan; Mahmud , Nurfarizan Mazhani; Abu, Nor ‘Asyiqin; Rosli, Siti Aisyah (International Journal of Accounting, Finance and Business, 2024)
The importance of corporate social responsibility (CSR) activities has become increasingly apparent, as many companies have had to cultivate their responses to reporting quality in order to maintain the reputation and standing of their companies in the business community. Therefore, understanding the factors that influence CSR reporting quality is vital for a company's survival in the long run. This study aims to examine the effect of corporate governance and family ownership on CSR reporting quality. This study was conducted on a sample of 306 firms listed on Bursa Malaysia based on seven industries from 2017 to 2018 using OLS regression. Results suggested that corporate governance and family ownership are positively linked with the quality of CSR reporting. The finding adds to the extant literature that the high quality of CSR could result from its effectiveness in corporate governance mechanisms. Companies with effective corporate governance would lessen uncertainty and attract more investors, hence improving the stakeholder’s understanding of the company’s activities. The finding also provides useful information to management in evaluating the impact of effective CG on CSR reporting quality, especially in the family-owned firm. As for family-owned firms persist competitive in the Malaysia market, these firm need to comply with good corporate governance practices according to the Malaysian Code on Corporate Governance (MCCG) guidelines. Managing internal and external stakeholder groups is critical for companies to remain visible, transparent, and district among their top competitors. Findings from this study can also be useful to relevant parties in reviewing current requirements, standards or policies related to CSR reporting quality.